2001
DOI: 10.1067/mtc.2001.115703
|View full text |Cite
|
Sign up to set email alerts
|

The adenosine triphosphate–sensitive potassium channel opener nicorandil protects the ischemic rabbit spinal cord

Abstract: Nicorandil has a protective effect on the ischemic rabbit spinal cord, and the beneficial effect seems mediated through the activation of adenosine triphosphate-sensitive potassium channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…This study was undertaken to evaluate the early and delayed pharmacological pre‐conditioning effect of diazoxide on spinal cord ischemia. We found that both early and delayed pharmacological pre‐conditioning induced by diazoxide were effective in reducing spinal cord ischemic injury in this rabbit model, which was devised by Zivin and DeGirolami (14) and has been confirmed by other investigators as a reliable model for producing neurologic deficits for ischemic spinal cord injury (15, 16). However, we were unable to find any difference between early and delayed pharmacological pre‐conditioning in terms of neurologic scores or normal motor neuron numbers.…”
Section: Discussionsupporting
confidence: 56%
“…This study was undertaken to evaluate the early and delayed pharmacological pre‐conditioning effect of diazoxide on spinal cord ischemia. We found that both early and delayed pharmacological pre‐conditioning induced by diazoxide were effective in reducing spinal cord ischemic injury in this rabbit model, which was devised by Zivin and DeGirolami (14) and has been confirmed by other investigators as a reliable model for producing neurologic deficits for ischemic spinal cord injury (15, 16). However, we were unable to find any difference between early and delayed pharmacological pre‐conditioning in terms of neurologic scores or normal motor neuron numbers.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, nicorandil (a K ATP channel opener) has a protective effect against ischaemia of the spinal cord in rabbits [24]. In addition, we have reported previously that acute hypoxia depresses excitatory synaptic transmission in the spinal cord by activating presynaptic adenosine A1 receptors [18].…”
Section: Introductionmentioning
confidence: 99%
“…9 These effects of nicorandil are known to dilate pericardial vessels. 17,18,24 For example, Heurteaux et al 17 reported that intracerebroventricularly administered nicorandil decreased neuronal cell degeneration in a rat model of transient global forebrain ischemia. In patients with ischemic heart disease, a 3-month nicorandil treatment improved flow-mediated brachial artery dilation, which indicates enhanced endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nicorandil is thought to exert an influence over the endothelial function in blood vessels. Wakamatsu et al 24 found that intravenous administration of nicorandil before ischemia protected rabbit spinal cord motor neurons and motor function. 13 In the present study, although we demonstrated that nicorandil prevented the endothelial dysfunction induced by acute smoking in rat cerebral arterioles, we did not measure the concentration or the activity of any NOS in the endothelium.…”
Section: Discussionmentioning
confidence: 99%